Elevated Expression of TLR2 in Aging Hearts Exacerbates Cardiac Inflammatory Response and Adverse Remodeling Following Ischemia and Reperfusion Injury - Zhai, Yufeng; Ao, Lihua; Yao, Qingzhou; The, Erlinda; Fullerton, David A.; Meng, Xianzhong (Frontiers in Immunology, 2022)
This study tested the hypothesis that Toll-like receptor 2 (TLR2) augments the inflammatory responses and adverse remodeling in aging hearts to exacerbate myocardial injury and cardiac dysfunction. Methods: Old (20-22 months old) and adult (4-6 months old) mice of C57BL/6 wild-type and TLR2 knockout (KO) were subjected to coronary artery ligation (30 minutes) and reperfusion (3 or 14 days). Left ventricle function was assessed using a pressure-volume microcatheter. Cardiac infarct size was determined by histology. Levels of vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), matrix metalloproteinase 9 (MMP 9), and collagen I in non-ischemic myocardium were assessed by immunoblotting. Monocyte chemoattractant protein-1 (MCP-1), keratinocyte chemoattractant (KC), and interleukin-6 (IL-6) levels in ischemic and non-ischemic myocardium were measured by enzyme-linked immunosorbent assay (ELISA). TLR2 expression in the myocardium of untreated wild type mice was also measured by immunoblotting. Results: Higher levels of MCP-1, KC, IL-6 were induced in both ischemic and non-ischemic myocardium of old wild type mice at day 3 and 14 following ischemia/reperfusion (I/R) than those of adult wild type mice. The hyper-inflammatory responses to I/R in aging hearts were associated with elevated levels of myocardial TLR2. TLR2 KO markedly down-regulated the expression of MCP-1, KC, IL-6, ICAM-1 and VCAM-1 in aging hearts at day 3 and 14 following I/R. The down-regulated inflammatory activity in aging TLR2 KO hearts was associated with attenuated production of MMP 9 and collagen I at day 14 and resulted in reduced infarct size and improved cardiac function. Conclusion: Elevated expression of myocardial TLR2 contributes to the mechanism by which aging exacerbates the inflammatory responses, adverse remodeling and cardiac dysfunction following myocardial I/R in aging.